Evaluasi Pembelajaran Berbasis Proyek: Analisis Mahasiswa dan Kualitas Produk Pembelajaran di Perguruan Tinggi - Hirnanda Dimas Pradana; Alim Sumarno; Utari Dewi; Citra Fitri Kholidya; Khusnul Khotimah (Postgraduate, University of Mataram, 2024)
This study aims to determine whether the implementation of project-based learning elevates product quality and student engagement levels. This study tries to find out the effect of project-based learning on product quality and the student engagement level in the learning process. During the conduct of the study, very few research methods were applied based mainly on observations. Observations were used to find levels of active engagement of students in project-based learning and assess the quality of their work. It would amount to observations conducted during the learning process for determining product quality in student-generated material. These observations would be made by checking the products against pre-designed criteria. The participants in this experiment were learners in classrooms specially reserved for the production of printed instructional materials. The participants in this experiment were the following people. From the findings of this study, it is concluded that project-based learning enhances not only what is learned but also the quality of whatever product is developed and student engagement with learning. An additional plus for project-based learning is that it really is a very effective way toward skill development among students. It further taps into student talent development. The recommendations that can be made to improve the implementation of project-based learning in tertiary institutions and better its effects on the learning by students.